Pragmatics in the health sciences - Garraffa, Maria; Mazzaggio, Greta (Cambridge elements, 2025)
This Element aims to address a gap in the literature at the intersection of linguistics, particularly pragmatics, and health sciences, such as speech and language pathology. The first section introduces the application of pragmatics concepts in healthcare and neuroscience. Section 2 discusses the development of pragmatic abilities in childhood, focusing on pragmatic communication disorder. Section 3 reviews studies on pragmatic abilities in adolescents, adults, and clinical populations, including assessments of pragmatic skills in ageing. Section 4 broadens the scope by exploring pragmatic impairments in new populations. The final section reflects on the importance of pragmatics in healthcare practice, introducing studies on mental health and intercultural pragmatics. Each section proposes discussion points to contextualise the research within debates on health pragmatics. The Element also includes a glossary (available as online supplementary material) to assist interdisciplinary audiences in understanding clinical pragmatics terminology